Biosorption of malachite green onto Haematococcus pluvialis observed through synchrotron Fourier‐transform infrared microspectroscopy. (1st October 2018) - Liu, J.H.; Zhang, L.; Zha, D.C.; Chen, L.Q.; Chen, X.X.; Qi, Z.M.
Abstract: Microalgae have emerged as promising biosorbents for the treatment of malachite green (MG) in wastewater. However, the underlying mechanism for the biosorption of MG onto microalgae is still unclear and needs further intensive study. In this work, synchrotron Fourier‐transform infrared (s‐FTIR) microspectroscopy in combination with biochemical assay is employed to evaluate MG removal efficiency (95·2%, 75·6% and 66·5%) by three stages of Haematococcus pluvialis . Meanwhile, the various vital changes of algal cells including lipids, proteins, polysaccharides and carotenoids is distinguished and quantified in situ . This study illustrates that s‐FTIR microspectroscopy is an effective and powerful tool to scrutinize the mechanism for the interactions between the MG dye and microalgal cells, and it even provides an effective and noninvasive new approach to screen potentially proper biosorbents for the removal of dyes from wastewater. Significance and Impact of the Study: Microalgae have potential application for their ability to absorb dyes from industrial wastewater. In this study, we initiated the application of synchrotron Fourier‐transform infrared (s‐FTIR) microspectroscopy to investigate malachite green dye removal efficiency by three stages of Haematococcus pluvialis, demonstrating that s‐FTIR is a very powerful tool in exploring the mechanism of the biosorption of dyes onto microalgae.